Factors Affecting Contractor Delays on Private Construction Projects in Trinidad and Tobago During COVID-19 - Sultan, Sarika (My University, 2021)
The Construction Industry of Trinidad and Tobago is currently facing significant delays due to the unanticipated Covid-19 Pandemic. Stakeholders are affected, especially contractors, since the Pandemic negatively impacted on the operations of active construction projects leading to temporary shutdowns and delays in completion dates. This study examines the effects of contractor delay factors on private construction projects in T&T during the Covid-19 Pandemic while also establishing solutions for mitigating them. The study also compares general contractor delay factors to Covid-19 contractor delay factors to determine their similarities or differences. The contributions of this paper fill the gaps in previous literature. A critical review of past literature, together with a questionnaire survey distributed to a sample population, was conducted to fulfil the research objectives. Along with a descriptive analysis, a statistical analysis including Relative Importance Index and Spearman’s Rank Correlation were used to analyse the data collected. The obtained results indicated that the top significant Covid-19 contractor delay factors were: international manufacturing and shipping challenges, local supply chain disruptions, rise in material prices, delays in material delivery, delays in original schedule, temporary shutdown and quarantining, payment delay due to cash flow challenges, fundamental uncertainties and unforeseen circumstances and workforce reductions as per social distancing requirements. Additionally, the main impacts of these factors were: increase in disputes, litigation, arbitration & claims; cost overrun, price escalations, loss of revenue; decreased labour productivity and efficiency rates; and job losses. The findings also determined the top mitigation measures which include: having a competent project manager, resource availability, investing in proper systems to plan and forecast finances/schedules, ensuring adequate and available source of finance until project completion, additional safety signs, professionals and systems, implementing sensors, tracking systems and advanced technology, and ensuring workers are vaccinated. Also, the comparison of the two sets of factors shows similarity
Keywords: Contractor delay; COVID-19; Pandemic; Mitigation measures; Safety; Contractor delay